THE DIVERSITY OF EPIPHYTIC FERN ON THE OIL PALM TREE (Elaeis guineensis Jacq.) IN PEKANBARU, RIAU - Sofiyanti, Nery (Jurnal Biologi Udayana, 2013)
Oil palm ( Elaeis guineensis ) is one  main commodity in Riau Province. Morphologically, the trunk of oil palm  has suitable environment for the growth of epiphytic fern, due to its broaden base of petiole that may accumulate organic and anorganic debrish. The objective of this study was to investigate the diversity of epiphytic fern on the oil palm tree. A total of 125 oil palm trees from seven  study sites in Pekanbaru, Riau were observed. The number of epiphytic ferns identified in this study was 16 species belongs to six families.
Keywords: epiphytic fern, oil palm tree, Pekanbaru